600,000 hectares of rice planted earlier in Vietnam to avoid risk to salinity intrusion brought by the 2019 El Nino - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
Based on directives issued by the MARD Vice Minister and the Department of Crop Production (DCP), the rice planting calendar in the Mekong River Delta(MRD) was adjusted to avoid salinity intrusion brought by the 2019 El Nino. The adjustments covering more than 600,000 hectares(Novemebr 2018 early planting reached 802,702 ha from 174,538 ha in 2017 and the December to February planting went down to 596,543 from 1,226,961 ha) were guided by climate-risk related maps and adaptation plans(CS-MAP) developed for the 13 provinces.